Frequency of 11q23/MLL gene rearrangement in Egyptian childhood acute myeloblastic leukemia: Biologic and clinical significance - Hagag, Adel Abdelhaleim (South Asian J Cancer, 2014)
BACKGROUND: Molecular cytogenetic abnormalities involving 11q23 are among the most common cytogenetic abnormalities in acute myeloid leukemia (AML) patients. AIM OF THE WORK: we aimed to evaluate the frequency of MLL/AF9 fusion gene in de novo AML patients, its impact on clinical features, and its prognostic significance. PATIENTS AND METHODS: Twenty-eight children patients with AML and 20 healthy controls were subjected to complete clinical examination and laboratory investigations including, complete hemogram and bone marrow (BM) examination. Diagnosis was based on FAB morphologic and immunophenotypic criteria. Detection of (MLL/AF9) fusion gene was assessed by dual color fluorescent in situ hybridization (FISH). Follow-up were carried out clinically and by blast count in BM, and response to therapy to detect the outcome of the disease. RESULTS: The incidence of MLL-fusion gene MLL/AF9 in AML cases was about (6/28) (21%). Four patients with MLL/AF9 fusion gene were newly diagnosed, two cases were at relapse and no patient at remission showed positivity. As regard the clinical outcome, five out of six MLL positive cases died, three of them during induction and two during relapse. The FAB AML subtypes with MLL/AF9 fusion were one M2, three M4, and two M5. CONCLUSION: MLL-fusion gene MLL/AF9 was found in about 21% of studied AML patients when assessed by FISH technique and this is of high clinical relevance as most of these abnormalities have been associated with poor prognosis.